(untitled) (Journal of Parents and Teachers, 2025)
What does it mean for us today to work, study, and enjoy ourselves using information and communication technologies? Does it feel like a challenge? Do they help us in our daily lives? Is it worth using them? No matter how personal each individual’s experience may be, we’ve all likely felt stressed and overwhelmed by technology at times, while in other moments, it has opened up a world of possibilities we never imagined. Have these new technologies come to change us? Do they improve our world and make processes easier? How can we use them in ways that are effective and fulfilling?